Experiência e narrativa no movimento cineclubista da década de 1970: "Corações e mentes" - Matela, Rose Clair Pouchain (2008)
I n this thesis, we collect the memories of the cineclub movement of the decade of 1970, through the narratives of life of some of its protagonists. We try to understand how this experience, despite under strong political repression, made possible to its participants the construction of collective actions, translated into a political-cultural practice that extended the spaces of exercise of the citizenship, putting in question the power of repression of the military dictatorship. We also consider that the cineclub movement consisted in a space of formation for the involved citizens, since the experience lived in the activity had as fundamental practice the research and the debate - space of intellectual construction and collective formation. Taking as reference the concepts of experience (erfahrung), memory and narrative of Walter Benjamin, the present work have as its main approach to reflect on the value of the experience as source and possibility of the narrative. We understand that the narratives constructed in the remembering process are manifestations of collective memories, since they are seen both as individual expressions - words, gestures, looks, voices, written and as cultural productions. They make possible to understand that the subjects subjectivize the culture, by having the capacity of reflection, of interpretation, meaning and re-meaning the world and its experiences in these mediations. We understand that the experiences, by inscribing itselves in the history of the societies, are inserted in a continuity/discontinuity, where if in one hand, we have the instituted social structures, on the other hand, we have what is instituted, what is (re) structured. In the tension between instituted and institutor, experiences appear, as the cineclub s, that go opposing to the emptying of the relations between the subjects, collaborating for the constitution of social processes that result of experiences that unfold, prolongate, interchange itselves. Experiences more compromised with human becoming.